Investigation of folate-conjugated fluorescent silica nanoparticles for targeting delivery to folate receptor-positive tumors and their internalization mechanism - Yang H; Lou C; Xu M; Wu C; Miyoshi H; Liu Y (International Journal of Nanomedicine, 2011)
Hong Yang1,*, Changchun Lou1,*, Mingming Xu1, Chunhui Wu1, Hirokazu Miyoshi2, Yiyao Liu1,31Department of Biophysics, School of Life Science and Technology, University of Electronic Science and Technology of China, Chengdu, Sichuan, People’s Republic of China; 2Radioisotope Research Center, University of Tokushima, Tokushima, Japan; 3Key Laboratory of Biorheological Science and Technology, Ministry of Education, Bioengineering College, Chongqing University, Chongqing, People’s Republic of China *These authors contributed equally to this work Abstract: Multifunctionalized nanoparticles (NPs) are emerging as ideal tools for gene/drug delivery, bioimaging, labeling, or intracellular tracking in biomedical applications, and have attracted considerable attention owing to their unique advantages. In this study, fluorescent silica NPs were synthesized by a modified Stöber method using conjugates of 3- mercaptopropyltrimethoxysilane (MPS) and maleimide-fluorescein isothiocyanate (maleimide-FITC). Mean diameters of the NPs were controlled between 212–2111 nm by regulating MPS concentration in the reaction mixture. Maleimide-FITC molecules were doped into NPs or conjugated to the surface of NPs through the chemical reaction of maleimide and thiol groups. The data showed that the former NPs are better than the latter by comparing their fluorescence intensity. Furthermore, folate molecules were linked to the FITC-doped silica NPs by using polyethylene glycol (PEG) (NH2-PEG-maleimide) as a spacer, thus forming folate receptor targeting fluorescent NPs, referred to as NPs(FITC)-PEG-Folate. The quantitative analysis of cellular internalization into different cancer cells showed that the delivery efficiency of KB cells (folate receptor-positive cells) is more than six-fold higher than that of A549 cells (folate receptor-negative cells). The delivery efficiency of KB cells decreased significantly after free folate addition to the cell culture medium because the folate receptors were occupied by the free folate. The NPs endocytosis mechanism was also investigated. It was shown that clathrin, an inhibitor of cell phagocytosis, markedly decreased the NPs uptake into KB cells, suggesting that it plays an important role in NPs cellular internalization. These results demonstrated that the novel particles of NPs(FITC)-PEG-Folate are promising for fluorescent imaging or targeting delivery to folate receptor-positive tumors. Keywords: fluorescent nanoparticles, silica, folate, targeted delivery, cellular internalization